THE INFLUENCE OF PRODUCT PRICE, SERVICE QUALITY, AND LOCATION ON PURCHASING DECISIONS AT SALSABILA MART STORE KARANGANYAR - Vesytha Peterria; LMS Kristiyanti; Maya Widyana Dewi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This study aims to determine the effect of product price, service quality, and location on purchasing decisions at Salsabila Mart Store, Gaum Tasikmadu Karanganyar. This research used a quantitative research method with data collection techniques through distributing questionnaires to consumers of Salsabila Mart Store. The population in this study consisted of 500 consumers, while the research sample was 100 respondents determined using the Slovin formula with a simple random sampling technique. The data analysis methods used included validity test, reliability test, classical assumption test, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²) with the assistance of SPSS version 23 application. The results of the study showed that partially, product price had a positive and significant effect on purchasing decisions with a t-value of 25.755 and a significance value of 0.000. Service quality also had a positive and significant effect on purchasing decisions with a t-value of 29.657 and a significance value of 0.000. In addition, location had a positive and significant effect on purchasing decisions with a t-value of 23.576 and a significance value of 0.000. Simultaneously, product price, service quality, and location significantly affected purchasing decisions with an F-value of 3219.681 and a significance value of 0.000. The coefficient of determination (Adjusted R Square) value of 0.990 indicated that the variables of product price, service quality, and location were able to explain purchasing decisions by 99.0%, while the remaining 1.0% was influenced by other variables outside this study